THERMAL NOISE AS ELECTROMAGNETIC POLUTAN IN WIRELESS COMMUNICATION SYSTEM - Rochman Ananda Arif S.; Rudy Yuwono; Endah Budi Purnomowati (Jurnal Mahasiswa TEUB, 2015)
In wireless communication system thermal noise is one of the noise that detected at the receiver. Thermal noise(Johnson Noise) exists in all resistors and results from the thermal agitation of free electrons therein by thetemperature.This paper starts with an introduction onhow temperature appears on the receiver and thermal noise onthereceiver. The major contribution factor to thermal noise power and RMS voltage is also discussed analytically. TheCDMA modem is used as a subject to study thermal noise in wireless communication system.